Risk of Ipsilateral Deep Vein Thrombosis After Use of AngioSeal Closure Device in Aneurysmal Subarachnoid Hemorrhage Patients - Addepalli, Aravind; Benton, Joshua; Zhu, Shaoyu; Mann, Shira Kaye; Fall, Mame P.; Cox, Andrew; Altschul, David J. (Elsevier Science Inc, 2020)
BACKGROUND: Deep vein thrombosis (DVT) is a known complication in patients with aneurysmal subarachnoid hemorrhage (aSAH). This study investigated the association between use of the AngioSeal (St. Jude Medical, Minnetonka, MN) vascular closure device and the risk of ipsilateral and any DVT event after angiography in patients with aSAH. METHODS: We conducted a review of our institutional cerebral angiography database for the years 2005-2018 to identify all adult patients who underwent angiography for aSAH. We compared the incidence of DVT (occurring within 14 days) between aSAH patients who underwent manual compression versus the AngioSeal closure device. RESULTS: A total of 459 aSAH patients underwent angiography; 262 underwent manual compression (57.1%) and 197 received AngioSeal (42.9%). There was a 3.4% rate of ipsilateral DVT in the manual compression group and 7.6% in the AngioSeal closure device group (chi 2 test, P = 0.04). Similarly, the rate of any DVT was 8.8% for manual compression and 16.8% for patients who received AngioSeal (chi 2 test, P = 0.01). On multivariate analysis, AngioSeal remained a significant independent predictor of ipsilateral DVT (odds ratio 2.4, P = 0.04) and any DVT (odds ratio 2.3, P = 0.01). CONCLUSIONS: In aSAH patients undergoing cerebral angiographic procedures with access through the femoral artery, the use of AngioSeal closure device was found to be associated with a significantly increased risk of ipsilateral DVT within 14 days.
Keywords: Aneurysm; AngioSeal; Closure device; Deep vein thrombosis; Subarachnoid hemorrhage